(untitled) (Computer systems and information technologies, 2023)
The quality of education in the field of information technology depends on the use of modern tools of cooperation between universities and leading companies. Micro-credentials, which are rapidly spreading throughout the world, are among the new innovative tools. On the example of the SoftServe company, the experience of using dual study, non-formal study, professional training of teachers is analyzed. Problems are identified and models of SoftServe cooperation with universities are described, which increase the employability of graduates.